Amostragem diurna versus noturna de ácaros (Arachnida: Acari) associados a Genipa americana L. (Rubiaceae) - Silva, Paulo Vittor Parecis [UNESP] (2014)
Community composition and abundance of plant and edaphic mites throughout nighttime are poorly known by the fact that studies are usually conducted only during the day. Thus, the objective of this study was to compare the diurnal and nocturnal community evaluating the possible influences of plant mites in the litter community. The research was conducted monthly from July 2012 to June 2013 in three areas in the municipality of São José do Rio Preto, SP. Twenty-one adult trees were selected for sampling in daytime and nighttime, and 10 leaves / tree / sample period were collected. In addition, part of the accumulated litter in the base of three Brazilian genipap plants in each of the three areas was collected. The areas were sampled always in the same order, Arboretum, Forest Grove 1 and Forest Grove 2, with daytime samplings between 8am and 11am and the evening samplings between 21pm and 23pm. 10,117 mites were collected during the day and 7,632 at night, distributed in 60 species. Euseius citrifolius Denmark & Muma and Euseius concordis Chant showed higher abundances in the daytime, while Agistemus floridanus Gonzalez presented a greater tendency to forage leaves at night. In leaf litter accumulated at the base of the Brazilian genipaps sampled, 4,168 mites were recorded during the day and 3,153 at night, identified in 95 species. The two species analyzed in this environment, Amblyseius aerialis Muma and Iphiseiodes saopaulus Denmark & Muma, have no significant differences in mean abundances between the two periods. The plant community showed no similarity with the litter community. Regarding the structure of the community, there was no difference between areas or between periods. The achieved results confirm that some species of mites have a different pattern of distribution between the periods studied, but the litter associated with genipap not act as refuge of these mites. Thus, the species that had lower abundance in the leaves in ...